PENGARUH MEDIA AUGMENTED REALITY BERBASIS ASSEMBLR EDU TERHADAP HASIL BELAJAR BANGUN RUANG PADA PESERTA DIDIK KELAS II SDN 20 INDARUNG - Nuraini, Darma; Safitri Syam, Salmaini; Amsari, Dina; Masniladevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the difficulties experienced by elementary school students in understanding the concept of three-dimensional shapes, which are abstract and require visualization skills. Therefore, appropriate learning media are needed to provide a more concrete and interactive learning experience. This study aims to determine the effect of Augmented Reality media using Assemblr Edu on students’ learning outcomes in three-dimensional shape material at SDN 20 Indarung. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of class II C as the experimental class and class II B as the control class. Data were collected through pretest and posttest assessments, as well as attitude and skill assessment instruments. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results showed that the use of Augmented Reality media using Assemblr Edu had a significant effect on students’ learning outcomes. The cognitive aspect obtained a t-count value of 2.752 > t-table 2.019, with an N-Gain score of 0.569 in the experimental class, which was higher than the control class (0.321). Furthermore, significant effects were found in the attitude aspect (t-count 2.3415 > t-table 2.019) and skill aspect (t-count 2.09692 > t-table 2.019). Thus, Augmented Reality media using Assemblr Edu can be an alternative mathematics learning medium to improve students’ conceptual understanding, attitudes, and skills in three-dimensional shape material through concrete, interactive, and meaningful learning experiences.